Growth of Nanocrystalline MoSe2 Monolayers on Epitaxial Graphene from Amorphous Precursors. Issue 2 (11th September 2018) - Göhler, Fabian; Hadland, Erik C.; Schmidt, Constance; Zahn, Dietrich R. T.; Speck, Florian; Johnson, David C.; Seyller, Thomas
Abstract : A new approach to the growth of MoSe2 thin films on epitaxial graphene on SiC(0001) by the use of modulated elemental reactants (MER) precursors has been reported. The synthesis applies a two‐step process, where first an amorphous precursor is deposited on the substrate which self‐assembles upon annealing. Films with a nominal thickness of about 1 ML are successfully grown on epitaxial graphene monolayer as well as buffer layer samples. Characterization of the films is performed using XPS, LEED, AFM, and Raman spectroscopy. The films are nanocrystalline and show randomly rotated domains. This approach opens up an avenue to synthesize a number of new van‐der‐Waals systems on epitaxial graphene and other substrates. Abstract : Two‐dimensional materials are an emerging field in materials science. Methods like MBE and CVD are being used to grow single layers of transition metal dichalcogenides and other materials. In this paper, a novel approach, which employs the deposition of calibrated elemental precursors is presented. Crystalline layers are then formed by self‐assembly of the elemental layers upon annealing. This so‐called modulated elemental reactants (MER) technique has been already established for the synthesis of complex, multilayered 3D heterostructures. Using the model system of MoSe2 on epitaxial graphene on SiC (0001), the 2D level is being targeted.